Platelet Indices as Surrogates for Bone Marrow Function in Thrombocytopenia - Pujari, Lahari; Duvvada, Divya; Pratti, Sesha Deepthi (Annals of Pathology and Laboratory Medicine, 2025)
Background: Thrombocytopenia is the decrease in circulating platelet count to below 150,000/mm³ typically resulting from either increased peripheral destruction or impaired production within the bone marrow. This study aims to evaluate the diagnostic utility of platelet indices-namely, Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), and Platelet Large Cell Ratio (P-LCR)-in differentiating hypoproductive from hyperdestructive causes of thrombocytopenia. Methods: A prospective, cross-sectional study was conducted over a two-year period involving 200 systematically sampled patients with thrombocytopenia. Platelet indices were measured using an automated hematology analyzer, and their values were statistically compared between hypoproductive and hyperdestructive groups. Results: The highest incidence of thrombocytopenia was observed in individuals aged 36-50 years, with a slight male predominance. Severe thrombocytopenia (platelet count <50,000/mm³) was noted in 94 cases (47%). The hyperdestructive group exhibited significantly higher mean values for MPV (10.70 fL vs. 9.22 fL), PDW (16.13 fL vs. 11.21 fL), and P-LCR (39.48% vs. 22.83%) compared to the hypoproductive group, with all differences reaching statistical significance (p<0.05). Bone marrow aspiration was performed in 13 of the 142 hyperdestructive cases, with 12 (92.3%) diagnosed as immune thrombocytopenic purpura (ITP). All 58 patients in the hypoproductive group underwent bone marrow evaluation, with megaloblastic anemia identified in 29 cases (50%). Conclusion: Platelet indices such as MPV, PDW, and P-LCR serve as valuable, non-invasive markers in the initial differentiation of thrombocytopenia etiology. Their routine use may aid in distinguishing between hypoproductive and hyperdestructive mechanisms, thereby guiding appropriate diagnostic workup and clinical management.